Late Holocene Paleomagnetic Secular Variation in the Chukchi Sea, Arctic Ocean. (9th May 2022) - West, Gabriel; Nilsson, Andreas; Geels, Alexis; Jakobsson, Martin; Moros, Matthias; Muschitiello, Francesco; Pearce, Christof; Snowball, Ian; O'Regan, Matt
Abstract: The geomagnetic field behavior in polar regions remains poorly understood and documented. Although a number of Late Holocene paleomagnetic secular variation (PSV) records exist from marginal settings of the Amerasian Basin in the Arctic Ocean, their age control often relies on a handful of radiocarbon dates to constrain ages over the past 4, 200 years. Here we present well‐dated Late Holocene PSV records from two sediment cores recovered from the Chukchi Sea, Arctic Ocean. The records are dated using 26 14 C measurements, with local marine reservoir corrections calibrated using tephra layers from the 3.6 cal ka BP Aniakchak eruption in Northern Alaska. These 14 C‐based chronologies are extended into the post‐bomb era using caesium‐137 dating, and mercury isochrons. Paleomagnetic measurements and rock magnetic analyses reveal stable characteristic remanent magnetization directions, and a magnetic mineralogy dominated by low‐coercivity minerals. The PSV records conform well to global spherical harmonic field model outputs. Centennial to millennial scale directional features are synchronous between the cores and other Western Arctic records from the area. Due to the robust chronology, these new high‐resolution PSV records provide a valuable contribution to the characterization of geomagnetic field behavior in the Arctic over the past few thousand years, and can aid in developing age models for suitable sediments found in this region. Plain Language Summary: Investigating past changes in Earth's magnetic field is important to understand how the field is generated and varies through time. Marine sediments can record geomagnetic field changes, and can be used to reconstruct past field behavior as long as they are well dated. There are few such records from the Arctic, particularly ones that have a robust chronology covering the past few thousand years. This study provides two new sedimentary paleomagnetic records from the Chukchi Sea of the Arctic Ocean, which were dated using radiocarbon and caesium‐137. Behavior of the geomagnetic field over the past 4, 200 years as preserved in the studied sediments matches the predictions of geomagnetic field models, and is also similar to other regional sedimentary records. Features that current models do not capture provide new information on variations of the geomagnetic field, and can be used to improve the models, and to date sediments from the region. Key Points: Geomagnetic field directions are reconstructed for two sediment cores from the Chukchi Sea for the past 4, 200 years The geochronology is based on 26 radiocarbon dates, 137 Cs and tephra from the Aniakchak CFE II eruption The records capture paleomagnetic features recognized in the western Arctic and could aid future geochronology